ANALYSIS OF THE ROLE OF DPD-RI SECRETARIAT STAFF IN BENGKULU PROVINCE - Herlinda Reski; Romdana (Universitas Negeri Medan, 2026)
This study is titled “Analysis of the Roles of Secretariat Staff at the DPD-RI Representative Office in Bengkulu Province.” One of the issues arising regarding the role of Secretariat staff at the DPD-RI Representative Office in Bengkulu Province is the suboptimal performance of their duties. In the implementation carried out by the secretariat staff of the DPD-RI Representative Office in Bengkulu Province, there are discrepancies with the processes or provisions established in the guidelines for managing DPD-RI offices in provincial capitals, as issued by the General Secretariat of the Regional Representative Council of the Republic of Indonesia in 2022. The purpose of this study is to identify, describe, and analyze the roles of the secretariat staff at the DPD-RI Representative Office in Bengkulu Province. This is a qualitative descriptive study; data were collected from informants selected using purposive sampling. Data collection was conducted using in-depth interviews, observation, and documentation. The results of the study indicate that the roles of the secretariat staff at the DPD-RI Representative Office in Bengkulu Province have been carried out in accordance with the implementation guidelines. However, improvements and refinements are still needed to ensure even better performance of these roles. To that end, the author recommends taking concrete steps to ensure the sustainable fulfillment of the roles of the Secretariat Staff of the DPD-RI Representative Office in Bengkulu Province, improving the quality of their work, and striving to provide specialized education or training. Keyword : Roles, Secretariat Staff, DPD-RI, Bengkulu